Prevalence of virulence- and antibiotic resistance-associated genotypes and phenotypes in Staphylococcus aureus strains from the food sector compared to clinical and cow mastitis isolates - Jurado, Andrea; Fernández, Lucía; Rodríguez, Ana; García, Pilar (Frontiers in Cellular and Infection Microbiology, 2024)
Infections by the pathogen Staphylococcus aureus currently represent one of the most serious threats to human health worldwide, especially due to the production of enterotoxins and the ability to form biofilms. These structures and the acquisition of antibiotic resistance limit the action of antibiotics and disinfectants used to combat this microorganism in the industry and the clinic. This work reports a comparative phenotypic and genotypic study of 18 S. aureus strains from different origins: clinical samples, milk from mastitic cows and food industry surfaces. Genetically, the strains were very diverse but, in most cases, a closer proximity was observed for those from the same source. Notably, the average number of virulence genes was not significantly different in strains from the food sector. Of the 18 strains, 10 coded for at least one enterotoxin, and four of them carried 6 or 7 enterotoxin genes. The latter were all veterinary or clinical isolates. Most strains carried prophages, plasmids and/or pathogenicity islands. Regarding antibiotic resistance, although phenotypically all strains showed resistance to at least one antibiotic, resistance genes were only identified in 44.5% of strains, being mastitis isolates those with the lowest prevalence. Virulence-related phenotypic properties such as haemolytic activity, staphyloxanthin production, biofilm-forming capacity and spreading ability were widely distributed amongst the isolates. Overall, our results indicate that production of virulence factors, antibiotic resistance and biofilm formation can be found in S. aureus isolates from diverse environments, including the food industry, although some of these traits are more prevalent in strains isolated from infections in cows or humans. This emphasizes on the importance of monitoring the spread of these determinants not only in samples from the clinical environment, but also along the food chain, a strategy that falls under the prism of a one-health approach.